Medium-term in situ experiment by using organic biocides and titanium dioxide for the mitigation of microbial colonization on stone surfaces. (September 2017) - Ruffolo, Silvestro A.; De Leo, Filomena; Ricca, Michela; Arcudi, Anna; Silvestri, Cinzia; Bruno, Laura; Urzì, Clara; La Russa, Mauro F.
Abstract: Organic biocides are commonly used to reduce the biocolonization on stone surfaces. However, it should be possible to prolong a new re-colonization by the use of a combined application of organic and inorganic active compounds. TiO2, thanks to its high chemical stability, non-toxicity, high photo-reactivity and low cost, make it a potential effective molecule for long-term biocide activity against several biofoulers. In this research, a multi analytical approach, including microscopy, cultural and molecular analyses, has been applied to monitoring the treated surfaces of the southeast wall of Villa dei Papiri in Ercolano. In this study case, organic conventional biocide has been used, followed by the application of newly formulated products based on pure and doped titanium dioxide nanoparticles. As control, one part of the wall was treated only with organic biocides before applying only the binder. Biological sampling was carried out during eight months, before and after the treatments with biocide, and after the treatments with undoped and doped TiO2 . The comparative analysis of results showed that microorganisms were drastically reduced after the biocide treatments, while the treatment with bare and doped TiO2 reduced a potential new recolonization. However, the effectiveness of the treatments was dependent on distance from the ground since high humidity reduced the efficiency of the treatments. Graphical abstract: Highlights: Titanium dioxide and silver nanoparticles have been applied in situ to prolong the effect of conventional as biocide. A multi-analytical approach have been applied to assess the efficacy of nanoparticles in situ. The mitigation of microbial colonization of nanostructured coatings have been tested in situ. The combination use of organic biocide and inorganic titania based ones can prolong the effect of treatments. High humidity may affect the efficiency of treatments.